Cooperative Operational Planning of Interruptible Load Contracts for Enhancing Performance Reliability of Multi-Microgrid Power Distribution Systems - Mahdi Farrokhi; Mahmoud Fotuhi-Firuzabad; Amir Safdarian; Payman Dehghanian (IEEE Access, 2024)
This paper evaluates the benefits of cooperative utilization of available flexibility for enhancing the performance reliability of Multi-Microgrid (MMG) distribution systems in emergency situations. Interruptible Load Contracts (ILCs) with voluntary load points, with the goal to reduce the penalty cost of unexpected power interruptions during fault events, are considered as the source of flexibility. In this paper, the business as usual where Microgrid Operators (MGOs) independently plan ILCs for emergency operations is compared with cooperative planning of ILCs shared among multiple MGOs. To do so, a mathematical optimization model is developed to optimally allocate ILCs to each MG considering the presence of other MGs in the MMG distribution system. Decision variables include the optimal location and size of ILCs in each MG for a given incentive rate that motivates customers’ enrollment. The model considers grid topological configuration, capacity, and voltage level as the main technical constraints. The model is formulated as a Mixed Integer Linear Programming (MILP) problem whose solution can be simply achieved via off-the-shelf software packages. Simulation results demonstrate the effectiveness of cooperative planning of ILCs in reducing the overall penalty costs of unexpected outages by 10% to 15% compared to the independent planning approaches, depending on the network characteristics.